2017
DOI: 10.1186/s12971-017-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer and tobacco smoking in Crete, Greece: reflections from a population-based cancer registry from 1992 to 2013

Abstract: BackgroundThe Cancer Registry of Crete is a regional population database that collects cancer morbidity/mortality data along with several risk factors. The current study assessed the geographical variation of lung cancer among ever and never smokers in Crete during the last 20 years.MethodLung cancer patient records (1992–2013) including information on medical history and smoking habits were obtained from the Cancer Registry of Crete. Age-Adjusted Incidence Rates (AAIR), prevalence of smoking among lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 36 publications
(37 reference statements)
1
15
0
2
Order By: Relevance
“…Increasingly, reports are showing that cigarette smoking and alcohol consumption are risk factors for lung cancer 25 , 26 . Our results showed that the ratios of cigarette smokers/nonsmokers in controls (88.4:11.6) and patients with lung cancer (60.5:39.5) were relatively normal, similar to the ratios of alcohol consumption/no alcohol consumption in controls and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, reports are showing that cigarette smoking and alcohol consumption are risk factors for lung cancer 25 , 26 . Our results showed that the ratios of cigarette smokers/nonsmokers in controls (88.4:11.6) and patients with lung cancer (60.5:39.5) were relatively normal, similar to the ratios of alcohol consumption/no alcohol consumption in controls and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tobacco prevention strategies should mainly target these smoking groups [67]. Generally, a shift towards less healthy behaviour was noticeable after the economic crisis, as has been observed in two recent Greek studies [72,73].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
“…Linking relevant complementary data sources can expand availability and utility of data variables that can add additional context to investigations and evaluations of populations of patients with cancer. A few population-based registries in the United States 7,35,36 and outside the United States 8,9,11 have used patient medical records to more fully capture patients’ smoking status. Using this approach, information about smoking was captured for between 43% and 92% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, information about smoking was captured for between 43% and 92% of patients. 79,11,36 Routinely abstracting information on smoking status from electronic medical records (EMRs) can be useful, even if the data are not complete. 8 However, depending on the EMR, this can require extensive time and effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation